Analysis of Sagarurung Smoked Fish Agroindustry Business Development Strategies in Fish Processing Groups in Talang Ubi District Penukal Abab Lematang Ilir Regency - Sadikin, Ali; Daud, Faizal; Wadjdi, Farid (Pascasarjana, Mataram University, 2024)
The objectives of this research are (1) To determine and analyze the strategy for developing the sagarurung smoked fish agroindustry business in the fish processing group in Talang Ubi District, PALI Regency; (2) Identify and identify the factors that influence the development of the smoked sagarurung fish agro-industry business in the fish processing group in Talang Ubi District, PALI Regency. This research was carried out in the sagarurung fish processing and marketing group in Talang Ubi District, PALI Regency. Based on the results of the research that has been carried out, it can be concluded that the most appropriate business development strategy to implement is: (a) Increasing the quality and quantity of sagarurung fish production so that it is able to compete with other business actors; (b) taking advantage of the government's role in supporting the development of the sagarurung fish business; (c) Innovating to always develop sagarurung fish products, attend training on how to package processed fish products properly and correctly; (d) Learn knowledge about technology in the production and marketing of a product. Utilizing technology as a medium for product dissemination; (e) Developing an information system for developing the sagarurung fish processing business